Influence of Extraction Method and Solvent Selection on Phytochemical Composition of Melia azedarach Root and Bark - Ponsian, J.K.; Sibuga, K.P.; Selemani, I.S. (International Journal of Applied Sciences and Biotechnology, 2025)
Melia azederach (chinaberry tree) is one of the plants with high abundant in phytochemicals, that can be extracted, purified, and packaged for developing bioherbicides. Despite the reported effectiveness of chinaberry extracts in controlling invasive weeds such as Kongwa weed, its bioactive compounds remain understudied. A study was conducted using factorial arrangement in a Completely Randomized Design to evaluate the phytochemical composition of the root and barks of chinaberry tree through soxhlet and maceration extraction techniques using three different solvents; methanol, ethanol and distilled water. The extraction processes were carried out following standard extraction methods to analyses concentration of phytochemicals in the plants. Qualitative analysis confirmed the presence of alkaloids, flavonoids, phenolics, saponins, tannins, glycosides, terpenoids, and steroids. Ethanol was the most effective solvent for extracting a broad spectrum of phytochemicals based on qualitative assessment, particularly from bark samples. On the other hands, quantitative analysis indicated that methanol provided the highest overall extraction efficiency across multiple phytochemical classes, with notable effectiveness for saponins and terpenoids. Water showed superior performance in extracting alkaloids and flavonoids, especially when Soxhlet extraction was employed.Maceration and Soxhlet extraction methods both yielded notable results, with ethanol-macerated bark exhibiting the highest levels of phenolics and tannins, and distilled water Soxhlet extraction yielding maximum flavonoid and alkaloid content. These findings confirm the potential of the chinaberry tree in on pesticide production. The study emphasizes the need for further research into compound isolation and bioactivity evaluation to harness the full therapeutic and industrial potential of this plant.Int. J. Appl. Sci. Biotechnol. Vol 13(3): 130-138.